Contribution of Estonian Architect Karl Tarvas (1885–1975), a Graduate of Riga Polytechnic Institute, to Estonian Housing During the Interwar Period - Mälk, Sandra (History of Engineering Sciences and Institutions of Higher Education, 2021)
Riga Polytechnicum (RP) / Riga Polytechnic Institute (RPI) was the only higher education institution in the territory of the present Baltic States where it was possible to obtain higher technical education in the 19th century and early 20th century. Well-known Estonian architects, engineers and industrialists also studied there. Karl Tarvas (1885–1975), a famous Estonian architect, studied at RPI from 1906 to 1915. His creative heritage significantly influenced and shaped the architecture of Tallinn and its suburbs in the 1920s and 1940s. During the Interwar period in the Republic of Estonia, K. Tarvas deliberately chose to improve the living conditions of the less affluent population by designing standard wooden buildings, which we now know as the Tallinn House (Estonian: Tallinna maja). This research provides an insight into the study years of K. Tarvas and critically evaluates his professional activity. K. Tarvas was one of the founders of Riga Estonian Students’ Society (Estonian: Riia Eesti Üliõpilaste Selts; REÜS) established in 1909, which united Estonian students at RPI. He also was among the creators of the Estonian Association of Architects (Estonian: Eesti Arhitektide Ühing) in 1921. His three sons Paul, Peeter and Pärtel also chose the profession of an architect, Peeter Tarvas (1916–1987) was the most prominent of the three.